The Influence of Work Discipline on the Employee Performance Study at Badan Kepegawaian Daerah - Kartikasari, Shanti; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine whether there is an influence of work discipline on the performance of study employees at Badan Kepegawaian Daerah Sidoarjo. The type of this research is quantitative associative. The sample in the study was 15 respondents, namely some employees of Badan Kepegawaian Daerah Sidoarjo. The instrument in this study used a questionnaire and data collection techniques by filling out a closed questionnaire. The data analysis technique used is multiple linear regression using the SPSS version 22 statistic program. The results of this study indicate that work discipline has a significant effect on the performance of the Badan Kepegawaian Daerah Sidoarjo employees with a t count > t table (2,603 ​​> 2,110).